PEMBERDAYAAN PEREMPUAN MELALUI KELOMPOK HOME INDUSTRY BERSINAR DALAM MENINGKATKAN PENDAPATAN EKONOMI KELUARGA ( Studi Pengolahan Oleh-oleh dari Lele Dumbo di Desa Sigi, Kecamatan Kahayan Tengah, Kabupaten Pulang Pisau) - Rida, Rida Nurjanah; Syamsuri, Dr. Syamsuri, M.Si (Universitas Palangka Raya, 2020)
Empowerment is a strategy in improving one's abilities and capacity to improve their lives to achieve prosperity through various potentials they have. Especially in the process of women's empowerment which is a strategy to increase the potential of women and increase the role of women in both the public and domestic domains. The existence of this Home Industry is one way for women to be directly involved in the empowerment process. The theory used is the theory of empowerment according to Nurshabani Katjasangkana with indicators namely access, participation, control and benefits. The research was conducted at the Home Industry souvenirs from processed African catfish in Sigi Village, Kahayan Tengah District, Pulang Pisau Regency. Data collection techniques used in the form of interviews, observation, and documentation. Analysis of the data used is data reduction, data presentation, and conclusion. And test the validity of the data using triangulation.The results of this study are that women's empowerment through the Home Industry group in increasing the income of the family economy study of processing of souvenirs from African catfish has been able to become a means for the Sigi Village community to carry out empowerment activities, so that this can improve family welfare. Then the supporting factors in the Home Industry activities consist of the existence of human resources, the existence of capital owned, the existence of good cooperation and the existence of facilities and infrastructure. While the inhibiting factor is marketing products that are still on a small scale.